Radioecological Monitoring of Radionuclides in Natural Waters of Sherabad River, Surkhandarya Region - Xolmurodov M. P. (Zien Journals, 2022)
The article presents studies on the radiometric determination of the beta-radiation activity of radionuclides of potassium-40 and thorium-232 isotopes in the waters of the Sherabad River in the Surkhandarya region. Six samples were taken from the water of the Sherabad River and measured with a radiometer-spectrometer MKGB01. The concentration of potassium-40 and thorium-232 isotopes in a sample taken from a river flowing near the village of Kallamozor was higher than at other points.
Keywords: radioactivity; radionuclide; beta-radiation; radiometer